2-3(7x+9)=6

Simple and best practice solution for 2-3(7x+9)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-3(7x+9)=6 equation:


Simplifying
2 + -3(7x + 9) = 6

Reorder the terms:
2 + -3(9 + 7x) = 6
2 + (9 * -3 + 7x * -3) = 6
2 + (-27 + -21x) = 6

Combine like terms: 2 + -27 = -25
-25 + -21x = 6

Solving
-25 + -21x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '25' to each side of the equation.
-25 + 25 + -21x = 6 + 25

Combine like terms: -25 + 25 = 0
0 + -21x = 6 + 25
-21x = 6 + 25

Combine like terms: 6 + 25 = 31
-21x = 31

Divide each side by '-21'.
x = -1.476190476

Simplifying
x = -1.476190476

See similar equations:

| 5n^2+n-5=0 | | N+4=3n+16 | | -5t^2+40t+20= | | 0.2r-1.3r+0.6=-0.9+3.6 | | 19/2/3 | | 2/3/18 | | 2k+2=-13+3k | | X+0.6x+0.03x=500 | | 1/5-1/6z=7/6 | | N-9=9+15 | | 4(3z+5)=10-2(z-5) | | 121^-1/2 | | 426=350t | | 2(1-7y)=4y+3 | | T-5+7+2k-3k=k-8 | | 6y+7=10y-3 | | 462=370x | | (36x^2y^4)^1/2 | | 4(3z-1)-3(z-8)=3(z-1) | | (T-2)/(4-t) | | -9+10x=4x+15 | | 9=12x^2-23x | | -77.08=9.4y | | 2x-1-4=0 | | -0.56m=4.592 | | 2.3x=14.582 | | 2c+4=14 | | 5/6z-100 | | 13-6m=4-6m | | 3^4/5*3^3/x | | 11k=13t-7k/2t | | 6b^2+48b=0 |

Equations solver categories